From the Commissary Dictator to the Katechon: Continuity in Carl Schmitt’s Theory of Intermediate Authority - Collison, Luke (Political theology, 2023)
What relation is there between the commissary dictator and the katechon in Schmitt’s writings? I argue that both the dictator of Dictatorship and the katechon of Nomos of the Earth are characterized by a specific conception of intermediate authority, which is central to Schmitt’s attempts, in the 1920s, to save the administrative apparatus of the state from its subsumption to the Rechtstaat's “machine of government”. Oriented by a concrete task and supported by a hierarchy of dignity, this limited personalist authority would preserve the creative humanity of the civil service. Informed by eschatological fragments from his Tagebücher, I argue that Schmitt’s 1920s works are haunted by a shadow of the katechon, only fleshed out in Nomos of the Earth. Despite shifts in weighting (from “decisionism” to “concrete-order thinking”) I argue that, in its dominant specificities, this form of authority returns in the doctrine of the katechon.